2000
DOI: 10.1002/(sici)1096-8628(20000320)91:3<180::aid-ajmg4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Three-year-old girl with partial trisomy 4p and partial monosomy 8p with resemblance to Brachmann-de Lange syndrome?another locus for Brachmann-de Lange syndrome on 4p?

Abstract: We describe a 3-year-old girl with partial trisomy 4p and partial monosomy 8p who had prenatal and postnatal growth retardation, mental retardation, no speech development, mild synophrys, hirsutism, apparently low-set ears, dysphonic hoarse voice, hyperactivity, and small hands with proximal placement of the thumbs. She had recurrent lung infections, due to earlier aspiration and immune deficiency (chronic granulomatous disease). Cytogenetic findings in this and other cases with suggestive phenotype may point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…The present experience in 2 patients with 4p trisomy/8p monosomy shows that their evolution is different from that seen in patients with Brachmann‐de Lange syndrome. These findings do not support the suggestion by Mau et al [2000] of an additional locus for Brachmann‐de Lange syndrome on the short arm of chromosome 4.…”
Section: To the Editorcontrasting
confidence: 99%
See 2 more Smart Citations
“…The present experience in 2 patients with 4p trisomy/8p monosomy shows that their evolution is different from that seen in patients with Brachmann‐de Lange syndrome. These findings do not support the suggestion by Mau et al [2000] of an additional locus for Brachmann‐de Lange syndrome on the short arm of chromosome 4.…”
Section: To the Editorcontrasting
confidence: 99%
“…In this journal, Mau et al [2000] described a 3‐year‐old girl with partial trisomy 4p (4pter → 4p12)/partial monosomy 8p (8p23 → 8pter) and clinical findings “suggestive of Brachmann‐de Lange syndrome.” By judging from the clinical photographs, this child presents the typical facial gestalt of patients with 4p trisomy and, as Wyandt et al [1993] stated, duplication of the region 4p16.1 to 4p16.3 is responsible for this typical craniofacial phenotype. The authors also described this girl as presenting prenatal growth retardation and microcephaly.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Differential expression of the BdLS phenotype in these two cases suggested that the BdLS phenotype is linked to the 9-Mb region spanning from 8p23.1 to 8p23, which includes the TNKS gene and overlaps with the 5Mb region recently proposed as responsible for this phenotype. 19,20 In addition, preserved GATA genes in the 11.7-Mb telomeric region could explain the absence of congenital heart defects in both of these patients. With regard to the phenotype of 9p duplication, the critical region for dysmorphic features has been identified in 9p22, 9,21 whereas the locus for intellectual impairment and epilepsy is assigned more distally from 9p23 to 9p24.3.…”
Section: Discussionmentioning
confidence: 90%
“…The dysmorphic features are subtle in this pure 4p trisomy, with a mildly bulbous nose, mild retrognathia, short philtrum, and fifth finger clinodactyly. No clinical features of the proband suggested Brachmann–de Lange syndrome, sometimes associated with trisomy 4p [Fryns, 2000; Mau et al, 2000]. Contrary to the 4p− syndrome, which is frequently associated with epilepsy, and in some cases West syndrome [Kanazawa et al, 1991], trisomy 4p is not described as a syndrome with seizures as a component.…”
Section: Discussionmentioning
confidence: 99%